Eufriesea zhangi sp. n. (Hymenoptera: Apidae: Euglossina), a new orchid bee from Brazil revealed by molecular and morphological characters - Nemésio, André; Júnior, José E. Santos; Santos, Fabrício R. (Zootaxa, 2013)
Eufriesea zhangi Nemésio & Santos Júnior sp. n. is described from the ‘Parque Nacional de Ubajara’, state of Ceará, northeastern Brazil. This orchid-bee species is superficially similar to the blackish species belonging to the Eufriesea mussitans (Fabricius, 1787) species-group. Molecular and morphological (both external and genital) characters were used to demonstrate that Eufriesea zhangi sp. n. is distinct from morphologically similar Eufriesea nordestina (Moure, 1999) and Eufriesea auriceps (Friese, 1899). Molecular data vaguely suggested that its closest relative is Eufriesea nigrohirta (Friese, 1899). This new species, as well as the recently described Eulaema quadragintanovem Nemésio & Ferrari, 2012, seems to be geographically restricted to ‘brejos de altitude’—Atlantic Forest physiognomies at the top of mountains in northeastern Brazil—in the state of Ceará. Due to their conspicuous isolation, these areas appear to be a rich source of unknown species that may rapidly vanish due to environmental disturbances.